TINDAK TUTUR ILOKUSI DALAM INTERAKSI JUAL BELI DI PASAR TEMPUREJO, JEMBER - Resti Purnama Sari; Akhmad Sofyan; A. Erna Rochiyati S. (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2020)
Tempurejo Market is a traditional market mostly visited by people who live in Tempurejo Village and its surroundings to varying the speech acts used. Sellers and buyers have an interesting narrative method or strategy so that they achieved a deal. The speech acts that are often used in buying and selling interactions at Tempurejo Market are illocutionary speech acts and bargaining strategies so that the research problem is how illocutionary speech acts and bargaining strategies are used between sellers and buyers in Tempurejo Market, Jember Regency. This study describes illocutionary speech acts and bargaining strategies in buying and selling interactions at this market. The method used in this research is descriptive and equivalent. The second method is used to match the data with illocutionary speech act theory. The results showed five kinds of illocutionary speech acts: assertive, directives, expressive, commissives, and declarative. Illocutionary speech acts often used in buying and selling interactions at Tempurejo Market are assertive speech and expressive speech. The bargaining strategies used in the buying and selling interactions at Tempurejo Market offer strategy, bargaining strategy, the bid approval strategy, and the seller strategy to reject the offering. The bargaining strategy often used in buying and selling interactions at Tempurejo Market is the offering strategy.